K + -Channels in Smooth Muscle Cells and Their Importance (Global Scientific Review, 2022)
K + -channels of smooth muscle cells play an important role in regulating membrane potential and their functional activity. So far, 4 different K + -channels are distinguished in smooth muscle cells. These include potential-dependent K + - channels, intracellular K + -channels, calcium-activated K + -channels (KCa-channels), and ATF-sensitive K + -channels.